Malignant Diseases in Ayurveda – A Review - Manjula; Chaudhary, Krutika (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Malignant diseases or cancer are rapidly spreading among the masses all over the world making it a cause of concern and creating the need of exploring it from varied perspectives aiming at discovering newer dimensions of its treatment. It is not a novel entity, the history being prevalent since vedic period. Methods: It is not mentioned as such in ancient Ayurveda texts, instead the matter is scattered here and there due to vastness of the disease and its ability to affect any part of the body. Hence, all the texts including brihattrayee and laghytrayi were critically reviewed to find each and every minute detail and elaborate the disease in view of types, etiology, pathogenesis, prodromal symptoms, symptoms, complications, and treatment. Results: It was observed that the disease was discussed under different headings in different chapters, the details reported in the article. Analysis: Ayurveda principles focus on specific pathogenesis of disease rather than mere nomenclature and has much to offer in cancer management. Discussion and Conclusion: The data will be beneficial to provide conceptual base of the disease, further enlightening the way to devise newer techniques and newer dravya to deal with the dreadly entity.